Lead generation for the complex sale : boost the quality and quantity of leads to increase your ROI - Carroll, Brian J. (Brian James), 1970- (McGraw-Hill, 2006)
This book presents a strategic, multi-modal approach to generating highly profitable leads. "Lead Generation for the Complex Sale" arms you with a proven approach to generating qualified leads for complex sales. The complex sale, a synthesis of consultative, competitive, and team selling that targets potential buyers for team service solutions, is the norm in today's B2B environment. You'll learn to define your ideal leads and target your sales approaches; align sales and marketing to optimize the number of leads; build strong lead pipelines; use multiple lead generation vehicles, including email, PR, referrals, speaking events; and more.